2004
DOI: 10.1111/j.1360-0443.2004.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social learning models of drug dependence: implications for the assessment of tobacco dependence in adolescents

Abstract: This paper is part of a series that has the goal of identifying potential approaches toward developing new instruments for assessing tobacco dependence among adolescents. The fundamental assumption underlying the series is that contemporary theories of drug dependence offer a rich source of opportunities for the development of theoretically based assessment tools. The present paper focuses on cognitive and social-learning models of drug dependence and the implications of these models for novel assessment instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
110
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 148 publications
3
110
0
2
Order By: Relevance
“…As such, emotional and sensory expectancies are central to conceptual models of cigarette smoking (e.g., Baker, Piper, McCarthy, Majeskie, & Fiore, 2004;Brandon, Herzog, Irvin & Gwaltney, 2004;Niaura, Goldstein, & Abrams, 1991;Witkiewitz & Marlatt, 2004). A number of studies have found that having higher positive outcome expectancies for smoking having to do with its stimulating, state enhancement, taste, and sensorimotor properties is associated with nicotine dependence (e.g., Copeland, Brandon, & Quinn, 1995;Kristjansson et al, 2011;Piper et al, 2004;Rohsenow et al, 2003;Vidrine et al, 2009), as well as withdrawal severity even after controlling for dependence (Vidrine et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As such, emotional and sensory expectancies are central to conceptual models of cigarette smoking (e.g., Baker, Piper, McCarthy, Majeskie, & Fiore, 2004;Brandon, Herzog, Irvin & Gwaltney, 2004;Niaura, Goldstein, & Abrams, 1991;Witkiewitz & Marlatt, 2004). A number of studies have found that having higher positive outcome expectancies for smoking having to do with its stimulating, state enhancement, taste, and sensorimotor properties is associated with nicotine dependence (e.g., Copeland, Brandon, & Quinn, 1995;Kristjansson et al, 2011;Piper et al, 2004;Rohsenow et al, 2003;Vidrine et al, 2009), as well as withdrawal severity even after controlling for dependence (Vidrine et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Drug expectancies can be understood as informational structures in long-term memory. [28][29][30] These fundamental elements of memory are theorized to both organize input to the central nervous system and guide management of behavior, acting as a "final common pathway" that is implicated in connections between a variety of prior conditions (for example, genetic predisposition, social influence, emotional state, personality) and drug use decisions 31,32 . Expectancies have been found to be robust predictors of drug use, including the initiation of cigarette smoking, 33,34 dependence 35 , and relapse after a period of abstinence.…”
mentioning
confidence: 99%
“…In addition, health-related outcome expectancies (or perceived health risks and benefits) are also fundamental constructs of many health behavior theories (Brewer et al, 2007;Weinstein, 1993), and smokers' healthrelated outcome expectancies of smoking and quitting are associated with a number of smoking-related constructs, such as intentions to smoke, decisions to start smoking, decisions to quit, and successful periods of abstinence (McKee, O'Malley, Salovey, Krishnan-Sarin, & Mazure, 2005;Romer & Jamieson, 2001;Weinstein, 2001). Many smoking-related intervention strategies capitalize on the relationship between health-related outcome expectancies and smoking behavior (Bize et al, 2012;Schlam & Baker, 2013).…”
Section: Introductionmentioning
confidence: 99%